Security of supply, case Finnish ports - Yliskylä-Peuralahti Johanna; Tapaninen Ulla (Curran Associates Inc., 2022)
Security of supply involves all the activities that are undertaken to secure a nations’ functioning and the welfare of its citizens in case of major disturbances and emergency situations. Maritime transports are very essential for Finland as over 80% of the foreign trade in the country is seaborne and possibilities to carry out these transports by other means of transport are limited. Any disruption in maritime transports has negative consequences to many sectors in the Finnish economy. With this paper we contribute to analysis on mitigation strategies of critical industries towards transport disruptions. Our case study concentrates on impacts of a port closure due to a strike in Finland in 2010 and companies’ strategies to manage their operations during the strike, and we draw conclusions to the general structure of mitigation strategies towards logistic vulnerability. The strike stopped approximately 80% of the Finnish foreign trade. We carried out personal interviews with representatives of the companies in Finnish critical industries to find out about the problems caused by the strike, how companies carried out their transports and how they managed to continue their operations during the strike. As a result of the strike Finnish companies could not export their products and/or import raw materials, components and spare parts, or other essential supplies. During the strike companies did various actions to secure their supply chains. The companies raised their inventory levels before the strike began, they rescheduled or postponed their deliveries, shifted customer orders between production plants among the company’s production network, or in the extreme case bought finished products from their competitor to fulfill their customers’ order. Our results also show that possibilities to prepare against transport disruptions differ between industries.